(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
On the one hand, suicide is a social phenomenon that depends on the structure of society, as a phenomenon of conscious termination of one’s life, unique only to humans. On the other hand, this is a person’s individual reaction to a difficult situation (psychological crisis), resulting from the characteristics of a particular person. The basis for providing psychological assistance to adolescents with suicidal behavior is a clear, deep and quick diagnosis of the teenager’s personality, his mental state, and level of suicidality. This allows him to accurately select methods and means of providing psychological assistance.